2008
DOI: 10.1002/anie.200802002
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Oxazaborolidinium‐Catalyzed Diels–Alder Reactions without CH⋅⋅⋅⋅O Hydrogen Bonding

Abstract: The oxazaborolidine Diels-Alder (DA) precatalysts first introduced by Corey et al. in 2002 [1] are remarkable for several reasons. The derived oxazaborolidinium cations, for example 1 a·HNTf 2 or 1 a·MX n (formed by exposure to either Brønsted [1][2][3] or Lewis [4] acids, Scheme 1), are active catalysts for enantioselective cycloadditions involving a broad range of dienes and dienophiles. [1][2][3][4][5][6][7][8][9][10][11][12] Perhaps the most significant quality of this family of Lewis acid (LA) catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…In this case, dienophiles lacking the typical hydrogen bond donor moiety required by Corey's pretransition state assembly model can also give rise to high enantioselectivities. These results echoed the previous study by Paddon-Row and co-workers on related cationic oxazaborolidine catalyzed Diels-Alder reaction without involvement of hydrogen bonding, in which other stereoelectronic effects may contribute to the preorganization of Lewis acid/carbonyl coordination [49]. Considering the Fig.…”
Section: Oxazaborolidine-based Catalystssupporting
confidence: 90%
“…In this case, dienophiles lacking the typical hydrogen bond donor moiety required by Corey's pretransition state assembly model can also give rise to high enantioselectivities. These results echoed the previous study by Paddon-Row and co-workers on related cationic oxazaborolidine catalyzed Diels-Alder reaction without involvement of hydrogen bonding, in which other stereoelectronic effects may contribute to the preorganization of Lewis acid/carbonyl coordination [49]. Considering the Fig.…”
Section: Oxazaborolidine-based Catalystssupporting
confidence: 90%
“…247 Key features of Corey‘s models include: (1) a preferred s-trans C=C-C=O conformation of the dienophile, (2) πstacking between the dienophile and the exo- phenyl group at C-5 of the catalyst, and (3) catalyst binding to the oxygen anti lone pair (with respect to the double bond) and formyl hydrogen in the case of aldehydes, versus catalyst binding to the syn oxygen lone pair and α-hydrogen of ketones, esters, and carboxylic acids. These different binding modes expose opposite faces of the dienophile and explain the opposite enantioselectivities observed experimentally.…”
Section: Lewis/brønsted Acid/hydrogen Bond Catalysismentioning
confidence: 99%
“…Recently, Paddon-Row et al reported a computational study of oxazaborolidinium-catalyzed intramolecular DA reactions which showed, among other things, that the Curtin-Hammett approximation holds in such catalyzed IMDA reactions and that predicted enantioselectivities, derived solely from differences in the transition structure free energies; the results were in good accord with the experimental enantioselectivities xi. This computational study extends the scope of that earlier work by investigating, using density functional theory (B3LYP/6-31G(d)), oxazaborolidinium-catalyzed intermolecular DA reactions of 1,3-butadiene with several different dienophiles, namely methacrolein ( 1 ), acrolein ( 12 ), methyl acrylate ( 13 ), dimethyl fumarate ( 14 ) and 2-methylbenzoquinone ( 15 ) (Figure 3).…”
Section: Introductionmentioning
confidence: 67%